Manejo de malezas en el cultivo de piña (Ananas comosus) en el Ecuador - Cunalata Cerezo, Freddy Omar (2022)
Pineapple cultivation in Ecuador represents an important sector of the productive area, due to the good export performance of the fruit, which has also allowed it to become the eighth largest supplier worldwide. Competition with weeds can aggravate the pineapple crop because, being smaller in appearance and offering a very slow initial vegetative growth, it favors the extraction of water (especially in regions influenced by long periods of drought) and nutrients by weeds. The most important weed species in pineapple cultivation are: Cynodon dactylon (L.) Pers), Ipomoea indica (Burm), Cyperus spp, Panicum maxcimum Jacq, Digitaria sanginalis L. Scop), Rottboellia cochinchinensis, Eleusine indica and Mimosa spp. The information obtained was carried out using the technique of analysis, synthesis and summary, with the purpose of providing the reader with knowledge about weed management in pineapple (Ananas comosus) cultivation in Ecuador. Based on the above, it was determined that the invasion of weeds in pineapple crops greatly reduces its production. Weeds compete with the plant for air, light, surface area and nutrients, which results in the formation of a thin stem that does not support the load of the fruit, causing it to tip over. To carry out an efficient weed control in pineapple crop it is important to take into account several factors: weed species, state of development of weeds and their relationship with the crop, control equipment, weather conditions and moisture content in the soil to initiate the respective control.